Secure Authentication System for Hybrid Cloud Service in Mobile Communication Environments - Jin-Mook Kim; Jeong-Kyung Moon (International Journal of Distributed Sensor Networks, 2014)
We want more cloud service because of computer resource reuse, server device cost, and space problems. So, related researchers suggest private cloud service to solve these problems in internetwork environment for only inner users. Therefore if outside users want to use private cloud service using mobile device, they do not support any services to outside user. Public cloud services can overcome private cloud services with the existing constraints. Amazon was the first public cloud service. In Korea, KT provide computing power and storage devices with payment. But this service is very expensive, so hybrid cloud service is developed. Hybrid cloud service operates mobile communication environment. User can contact to service using smart phone, tablet and PC. So, it has many security threats such as internet environment with server-client system. Furthermore, mobile device user wants more nomadic attribute and free contact to server through outside communication environments. So it can make many security problems to server. Therefore researcher must solve security threats in mobile communication environment with hybrid cloud service system. But now anybody have no idea about these problems. In this paper, we approach to user and mobile device authentication system with hybrid cloud service server. They have smart phone, Tablet, Ultrabook and PC to uses hybrid cloud service such as attribute based services. Our proposed authentication system can support user authorization, device certification and service authentication service to user very easily. It uses RADIUS method and Two-factor authentication schemes. So, we propose a secure authentication system for the hybrid cloud service in mobile communication environments in this paper. Our proposal scheme can provided security, availability, applicability, and resistance about Man-In-The-Middle attack.